The role of social costs in response to labor market opportunities: Differences across race - Kalee E. Burns; Julie L. Hotchkiss (Federal Reserve Bank of Atlanta, 2023)
Using the American Community Survey between 2005 and 2019, this paper investigates the role constraints to migration might play in explaining racial/ethnic disparities in the labor market. We find that Black workers are typically less responsive than White workers to changes in job opportunities, but responsiveness increases when those opportunities present themselves in locations with a higher share own-minority population. We construct an education/race specific Bartik shift-share instrument to control for potential endogeneity of growth in job opportunities.
Keywords: J61; J15; J18; 330; racial labor market disparities; migration costs; Delta index; social costs; place-based; people-based; mismatch